Evaluation of novel ventricular repolarization parameters in patients with acromegaly - Eren, Hayati; Genç, Selin; Evren, Bahri; Şahin, İbrahim (The European Research Journal, 2023)
Objectives: T wave’s peak and end interval (Tp-e), Tp-e/QT ratio and Tp-e/QTc ratio are novel markers of ventricular repolarization and are associated with ventricular arrhythmias. Increased ventricular arrhythmia incidence is reported in patients with acromegaly. The purpose of this study is to evaluate ventricular repolarization using the Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio in patients with acromegaly. Methods: Thirty-five patients with acromegaly were included in the study. The control group was consisted of forty-one subjects without acromegaly that having similar age, sex ratio and comorbidities. The Tp-e interval, Tp-e/QT ratio, Tp-e/QTc ratio, and other ventricular repolarization parameters of all patients were evaluated using electrocardiography. Results: Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio were significantly prolonged in patients with acromegaly compared to the control group. Furthermore, Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio showed a significant correlation with plasma GH levels and LVMI values. Conclusions: Our study revealed that Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio are prolonged in patients with acromegaly. We believe that the Tp-e interval, Tp-e/QT ratio, and Tpe/QTc ratio can be used in the evaluation of increased cardiovascular risk in patients with acromegaly.